Climbing Plant‐Inspired Micropatterned Devices for Reversible Attachment. (21st July 2020) - Fiorello, Isabella; Tricinci, Omar; Naselli, Giovanna Adele; Mondini, Alessio; Filippeschi, Carlo; Tramacere, Francesca; Mishra, Anand Kumar; Mazzolai, Barbara
Abstract: Climbing plants have evolved over millions of years and have adapted to unpredictable scenarios in unique ways. These crucial features make plants an outstanding biological model for scientists and engineers. Inspired by the ratchet‐like attachment mechanism of the hook‐climber Galium aparine, a novel micropatterned flexible mechanical interlocker is fabricated using a 3D direct laser lithography technique. The artificial hooks are designed based on a morphometric analysis of natural hooks. They are characterized in terms of pull‐off and shear forces, both in an array and as individual hooks. The microprinted hooks array shows high values of pull‐off forces (up to F ⊥ ≈ 0.4 N cm −2 ) and shear forces (up to F// ≈ 13.8 N cm −2 ) on several rough surfaces (i.e., abrasive materials, fabrics, and artificial skin tissues). The contact separation forces of individual artificial hooks are estimated when loads with different orientations are applied (up to F ≈ 0.26 N). In addition, a patterned tape with directional microhooks is integrated into a mobile platform to demonstrate its climbing ability on inclined surfaces of up to 45°. This research opens up new opportunities for prototyping the next generation of mechanical interlockers, particularly for soft‐ and microrobotics, the textile industry, and biomedical fields. Abstract : Climbing plant‐inspired flexible micropatterned devices for reversible attachment are developed using a two‐photon lithography microfabrication technique. The devices can strongly interlock with several rough surfaces, such as abrasive materials, fabrics with different textures (e.g., Velcro‐loop and woven polyester), and soft skin tissues. Furthermore, the high shear‐dependent devices demonstrate great potential for climbing robot applications.